Suzuki-Wardowski Type Theorems for Generalized α-η-GF-Contractions: Vo Thi Le Hang, Kanokwan Sitthithakerngkiet - Team, Support (Thai Journal of Mathematics, 2021)
The notion of a generalized α-η-GF-contraction is introduced and Suzuki-Wardowski type theorems for generalized α-η-GF-contractions are proved. These results generalize and improve the main results of [D. Wardowski, N.V. Dung, Fixedpoints of F-weak contractions on complete metric spaces, Demonstratio Math. 47 (1) (2014) 146–155, N.V. Dung, V.T.L. Hang, A fixed point theorem for generalized F-contractions on complete metric spaces, Vietnam J. Math. 43 (4) (2015) 743–753, N. Hussain, P. Salimi, Suzuki-Wardowski type fixed point theorems for α-GF-contractions, Taiwanese J. Math. 18 (6) (2014) 879–1895]. An application to the Urysohn integral equation is obtained. Examples are also given to illustrate obtained results.